Percepatan Penurunan Stunting Melalui Edukasi PHBS Rumah Tangga pada Masyarakat Desa Owata - Ayu Rofia Nurfadillah; Madania Madania; Ariani Hutuba (Universitas Negeri Gorontalo, 2023)
Abstract Gorontalo Province is included in the top 10 provinces with the highest stunting cases nationally. Based on the Indonesian Nutrition Status Study (SSGI), the stunting rate in Gorontalo Province in 2021 will reach 29%. Furthermore, the SSGI data shows that the prevalence rate of stunting in Bone Bolango Regency is 25.1 percent. The high number of stunting cases in Bone Bolango Regency is of great concern to both lecturers and students of KKN-PK at Gorontalo State University in 2022 to make several efforts to reduce stunting in Bone Bolango Regency, this also supports the Gorontalo Province BKKBN Program in terms of accelerating stunting prevention in the Regency area. Bone Bolango. According to BKKBN data, Owata Village is one of the villages that will become a locus of stunting in 2022, the number of stunting in Owata village is 12 toddlers. The KKN PK activities were carried out for 42 days starting from November 30 2022 to January 7 2023 in Owata Village, Bulango Ulu District, Bone Bolango Regency with a total of 12 KKN PK participants. The stages of the activities carried out include field observations, initial surveys, discussions and interviews, initial seminars as well as FGDs with the community, village assistants and village officials to explain the KKN PK program that will be carried out in the village and determine additional programs from the community, implementation of the KKN program PK is PHBS education to the community which consists of CTPS socialization activities for children at SDN 9 Bulango Ulu and household PHBS socialization to the Owata community and the final activity is monitoring and evaluation. The target of this program is to increase public awareness in implementing PHBS so that it can reduce stunting cases in Owata Village. AbstrakProvinsi Gorontalo termasuk dalam 10 besar Provinsi dengan kasus stunting tertinggi Nasional. Berdasarkan Studi Status Gizi Indonesia (SSGI), angka stunting di Provinsi Gorontalo pada tahun 2021 mencapai 29%. Selanjutnya data SSGI menunjukkan angka prevalensi stunting di Kabupaten Bone Bolango sebesar 25,1 persen. Tingginya kasus stunting di Kabupaten Bone Bolango menjadi perhatian besar baik bagi dosen dan mahasiswa KKN-PK Universitas Negeri Gorontalo Tahun 2022 untuk melakukan beberapa upaya penurunan stunting di Kabupaten Bone Bolango, hal ini juga mendukung Program BKKBN Provinsi Gorontalo dalam hal percepatan pencegahan stunting di wilayah Kabupaten Bone Bolango. Menurut Data BKKBN Desa Owata merupakan salah satu desa yang menjadi lokus stunting pada tahun 2022, jumlah stunting di desa owata adalah 12 balita. Kegiatan KKN PK dilaksanakan selama 42 hari dimulai tanggal 30 November 2022 sampai dengan 7 Januari 2023 di Desa Owata, Kecamatan Bulango Ulu, Kabupaten Bone Bolango dengan jumlah peserta KKN PK sebanyak 12 orang. Adapun tahapan kegiatan yang dilaksanakan antara lain, observasi lapangan, survey awal, diskusi dan wawancara, seminar awal sekaligus FGD bersama masyarakat, pendamping desa dan aparat desa untuk memaparkan program KKN PK yang akan dilaksanakan di desa dan menetapkan program tambahan dari masyarakat, pelaksanaan program KKN PK yaitu edukasi PHBS pada masyarakat yang terdiri dari kegiatan sosialisasi CTPS pada anak SDN 9 Bulango Ulu dan sosialisasi PHBS Rumah Tangga pada masyarakat Owata dan kegiatan akhir yaitu monitoring dan evaluasi. Target program ini yaitu meningkatnya kesadaran masyarakat dalam menerapkan PHBS agar bisa menurunkan kasus stunting di Desa Owata.